Innate immune activation of the NLRP3 inflammasome pathway drives tau pathology: The role of microglia activation in the development of amyloid and tau pathology in Alzheimer's disease. (7th December 2020) - Ising, Christina; Venegas, Carmen; Zhang, Shuangshuang; Scheiblich, Hannah; Schmidt, Susanne V.; Vieira‐Saecker, Ana; Schwartz, Stephanie; Albasset, Shadi; McManus, Roisin M.; Tejera, Dario; Griep, Angelika; Santarelli, Francesco; et al.
Abstract: Background: Alzheimer's disease is characterized by the extracellular accumulation of amyloid beta (Aß), intraneuronal formation of neurofibrillary tangles made of hyperphosphorylated tau and activated microglial cells, the innate immune cells of the brain. Activation of microglia by Aß or other DAMPs results in the assembly of the NLRP3 inflammasome consisting of NLRP3, ASC and Caspase‐1. This leads to subsequent production and secretion of inflammatory mediators including IL‐1β and ASC specks. Here, we investigate a contribution of the NLRP3 inflammasome to the development and progression of tau pathology. Method: Tau22 transgenic mice, that express human 4‐repeat tau mutated at sites G272V and P301S under a Thy1.2‐promotor, were crossed into either NLRP3 inflammasome knockout or ASC knockout mice and analyzed before development of tau pathology (3 month of age) and when robust tau pathology is present (11 month of age). Animals underwent behavioral phenotyping, analysis of pathology as well as assessement of microglial activation. Additionally, Tau22/NLRP3‐knockout and Tau22/ASC‐knockout mice received an injection of Aß‐containing APP/PS1 mouse brain derived lysates to study Aß‐induced spreading of tau pathology. For in vitro studies, primary mouse microglia were treated with different forms of tau and analyzed for NLRP3 inflammasome activation. Result: NLRP3 inflammasome activation was increased in fronto‐temporal dementia patients as well as in Tau22 mice. Knockout of ASC or NLRP3 in Tau22 mice decreased levels of active tau kinases while increasing activity of phosphatase PP2A in the hippocampus. This strongly protected from accumulation of hyperphosphorylated, misfolded tau in ASC knockout and more robustly in NLRP3 knockout mice while attenuating behavioral deficits. Furthermore, loss of NLRP3 inflammasome function ameliorated Aß‐induced tau pathology. In vitro, treatment of microglia with tau‐containing mouse brain homogenates or recombinant tau monomers and oligomers resulted in IL‐1β release in a NLRP3‐dependet manner, most likely mediated via TLR4. However, the same concentration of recombinant tau fibrils did not evoke this response. Conclusion: These findings are in line with the hypothesis that innate immune activation represents an important pathogenic factor for tau pathology. In Alzheimer's disease, early Aß deposition may cause subsequent tau pathology and neuronal demise through NLRP3‐mediated innate immune pathways.